2010
DOI: 10.5580/26a7
|View full text |Cite
|
Sign up to set email alerts
|

The Internet and Pet Health Information: Perceptions and Behaviors of Pet Owners and Veterinarians

Abstract: Introduction: The current study assesses the online search behavior of pet owners for pet health information and the perception of clients' internet use by their veterinarians.Materials and methods: A random sample of veterinary clinics was selected from two metropolitan US areas. Results and Conclusions: The majority of clients reported using the internet for pet health information with positive results. Veterinarians expressed concern over clients' ability to understand medical information and the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…This is a similar finding to Kogan et al (4) who found that for US veterinarians, 63.5% perceived that 0–40% of clients understand online information, compared to 73% in this study. Similarly, Kogan et al (4) found 62.9% of veterinarians perceived that between 41 and 80% of clients trusted what they read online compared to 72% in this study. Importantly, 40% of veterinarians stated that the Internet has a negative impact on companion animal health.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is a similar finding to Kogan et al (4) who found that for US veterinarians, 63.5% perceived that 0–40% of clients understand online information, compared to 73% in this study. Similarly, Kogan et al (4) found 62.9% of veterinarians perceived that between 41 and 80% of clients trusted what they read online compared to 72% in this study. Importantly, 40% of veterinarians stated that the Internet has a negative impact on companion animal health.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, 40% of veterinarians stated that the Internet has a negative impact on companion animal health. This compares to 23.1% of veterinarians in the US that stated the Internet had a negative impact on pet health (4). This could be due to the wide range of online information sources which are available and with a varying quality of information, especially when this information could involve complex pet health issues.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations